Dwelling in the deep – strongly increased root growth and rooting depth enhance plant interactions with thawing permafrost soil - Blume-Werry, Gesche; Milbau, Ann; Teuber, Laurenz M.; Johansson, Margareta; Dorrepaal, Ellen (The New phytologist, 2019)
Climate-warming-induced permafrost thaw exposes large amounts of carbon and nitrogen in soil at considerable depths, below the seasonally thawing active layer. The extent to which plant roots can reach and interact with these hitherto detached, deep carbon and nitrogen stores remains unknown. We aimed to quantify how permafrost thaw affects root dynamics across soil depths and plant functional types compared with above-ground abundance, and potential consequences for plant–soil interactions. A decade of experimental permafrost thaw strongly increased total root length and growth in the active layer, and deep roots invaded the newly thawed permafrost underneath. Root litter input to soil across all depths was 10 times greater with permafrost thaw. Root growth timing was unaffected by experimental permafrost thaw but peaked later in deeper soil, reflecting the seasonally receding thaw front. Deep-rooting species could sequester 15N added at the base of the ambient active layer in October, which was after root growth had ceased. Deep soil organic matter that has long been locked up in permafrost is thus no longer detached from plant processes upon thaw. Whether via nutrient uptake, carbon storage, or rhizosphere priming, plant root interactions with thawing permafrost soils may feed back on our climate both positively and negatively.